A denoising scheme for DSPI phase based on improved variational mode decomposition. (15th September 2018) - Xiao, Qiyang; Li, Jian; Zeng, Zhoumo
Graphical abstract: Highlights: The IVMD is proposed to decompose DSPI phase map. An adaptive mode threshold method is proposed for selecting noise-free components. The IVMD method can determine the most suitable decomposed mode number. This proposed method can effective reduce DSPI phase noise. Abstract: Aiming at reducing the noise interference of digital speckle pattern interferometry (DSPI) phase map, a DSPI phase denoised method based on improved variational mode decomposition (IVMD) is proposed in this paper. Firstly, the IVMD method is adopted to decompose DSPI phase map and obtain the optimal mode components; Then, according to the mode components characteristics, an adaptively mode threshold method is proposed to process the mode components. Finally, the denoised mode components are reconstructed to obtain the denoised DSPI phase map. The result indicates that the proposed method can effectively filter out noise interference, and the peak signal-to-noise ratio (PSNR) is higher than other denoised methods.